MENENTUKAN JUMLAH BENDUNGAN DI INDONESIA SAM PAl DENGAN TAHUN 2005 DAN ANALISIS KOMPOSISINYA - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 2006)
Dams are very useful for human being, so there are 45.000 dams in operation all over the world at the end of 2000. However rightnow the number of dams already in operation in Indonesia are still unclear, people used their olVn computation. Actually only 5,3 % of the total hydro electric pOlVer already developed from total hydro power potential available in Indonesia, while dam is the main component of large hydro electric power plants, it mean that the opportunity for large hydro electric power plants as well as dams development still very promising. Besides, dams are also needed for irrigation works, water supply, and the like. That's why these data of water resources will be described as well. To continue dam development, many data are needed, amongst others data of dams already in operation. These important data could be used for design, construction, operation and maintenace if we kwow all the dams already completed and in operation. If something happen,can be visited the dams which more or less in the same conditions. So it is very important to conduct research, prepare tables and compute the number of dams already in operation. This paper describes the computation alreL...'ydone, which hopefully usefulfor the readers.